(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
Milk thistle, Silybummarianum (L.)Gaertn.,is grown throughout the world for its hepatoprotectant flavonolignans, known collectively as silymarin. Silymarin is found primarily in the seeds. Milk thistle was grown outdoor field for determination of plant growth, seed yield under various variants of row spacing (30x20, 40x20 and 50x20) and different sowing dates (May 20, May 30 and June 10). Plant height measured (ranging from 43.5-82.6cm)and yield (ranging from 5.24-70.31cg/ha) that there was a significant difference among different sowing dates and row spacing. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 73-75